Mecanismos de HARQ usando códigos LDPC com retransmissão parcial e combinação por diversidade - Uchôa, Andre Gustavo Degraf (2011)
Modern standards of communication systems are including in their standards retransmission mechanisms. This work presents mechanisms for retransmission of packets by simpler and more efficient than the classical mechanisms of packet retransmissions. The proposed schemes are presented that use packet retransmission with partial retransmission and diversity combining. In addition, theoretical analysis will be presented to validate the results of the simulations. These theoretical analysis are obtained through the analysis EXIT charts and mutual information. The results and analysis were performed on channels such as AWGN and Block-Fading. The computational complexity, ease implementation and low average energy consumption for transmission of the proposed methods are some of the reasons they become interesting both for academia and for industry.